1994
DOI: 10.1017/s0022215100128713
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosacroma of the vocal fold: a late complication of radiotherapy

Abstract: The carcinogenic effect of ionizing radiation is a well known phenomenon. However, the induction of malignancies following irradiation for head and neck cancers is quite rare (Steeves and Vataini, 1982). Most reported cases are osteogenic sarcomas with soft tissue sarcomas encountered less often.We report a rare case of fibrosarcoma of the larynx, following radiation therapy for glottic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…In 1978, Donaldson 17 described a fibrosarcoma of the larynx arising at the site of a squamous cell carcinoma previously treated by radiotherapy. A similar case was reported in 1994 by Nageris et al, 25 who described a rare case of f ibrosarcoma of the vocal cord extending into and obliterating the paralaryngeal space, following radiotherapy for a glottic squamous cell carcinoma. In 1984, Ferlito et al 19 reported a metachronous coexistence of laryn- geal mucosa-associated lymphoid tissue (MALT) lymphoma (of a low grade of malignancy) and squamous cell carcinoma, with the term "pseudolympho- An apparent association of epithelial and mesenchymal neoplasms of the larynx is not always confirmed on closer scrutiny; for example, it is important to distinguish solitary tumors manifesting bidirectional or multidirectional differentiation from true synchronous primary cancers of the larynx originating from 2 discrete, different malignant clones.…”
supporting
confidence: 78%
“…In 1978, Donaldson 17 described a fibrosarcoma of the larynx arising at the site of a squamous cell carcinoma previously treated by radiotherapy. A similar case was reported in 1994 by Nageris et al, 25 who described a rare case of f ibrosarcoma of the vocal cord extending into and obliterating the paralaryngeal space, following radiotherapy for a glottic squamous cell carcinoma. In 1984, Ferlito et al 19 reported a metachronous coexistence of laryn- geal mucosa-associated lymphoid tissue (MALT) lymphoma (of a low grade of malignancy) and squamous cell carcinoma, with the term "pseudolympho- An apparent association of epithelial and mesenchymal neoplasms of the larynx is not always confirmed on closer scrutiny; for example, it is important to distinguish solitary tumors manifesting bidirectional or multidirectional differentiation from true synchronous primary cancers of the larynx originating from 2 discrete, different malignant clones.…”
supporting
confidence: 78%
“…There are sporadic reported cases of RIS, such as osteosarcoma and angiosarcoma [4,5]. Nageris et al [6] reported fibrosarcoma as a late complication of radiotherapy. In this case, the patient appeared with fibrosarcoma 5 years after laser surgery and radiotherapy of laryngeal squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Radyoterapi sonrası tedavi amacıyla da olsa radyasyon uygulanan alanlarda, ilk tümörden farklı histolojik tiplerde ikinci tümör gelişen olgular da bildirilmiştir. 2 Literatürdeki bu vakaların büyük kısmı osteojenik sarkomlardır. Baş boyun malignitelerinin tedavisinde radyoterapi oldukça sık kullanılır.…”
Section: Introductionunclassified